Methodological Approaches to Studying Risk Factors for Adverse Events Following Routine Vaccinations in the General Population and Vulnerable Subgroups of Individuals Using Health Administrative Data - Hawken, Steven (Université d'Ottawa / University of Ottawa, 2014)
Objectives: This thesis included 6 manuscripts which focused on the analysis of adverse events following immunization (AEFIs), including general health services utilization (emergency room (ER) visits and hospital admissions) and specific diagnoses (e.g. febrile convulsions). The main objectives of this research were: 1) To demonstrate the utility of the self-controlled case series (SCCS) design coupled with health administrative data for studying the safety of vaccines; 2) Introducing an innovative approach using relative incidence ratios (RIRs) within an SCCS analysis to identify risk factors for AEFIs and to overcome the healthy vaccinee bias; and 3) To demonstrate how SCCS and RIR analyses of health services outcomes in health administrative data can provide important insights into underlying physiological and behavioural mechanisms. Data Sources: This work utilized Ontario health administrative data housed at the Institute for Clinical Evaluative Sciences (ICES). The study included all children born in Ontario, Canada between 2002 and 2011 (over 1 million children). Vaccinations were identified using OHIP fee for service billing codes for general vaccination. Admissions and ER visits for any reason were identified in the Discharge Abstract Database (DAD) and National Ambulatory Care Reporting System (NACRS). Primary reasons for admissions and ER visits were investigated using ICD-10-CA codes reported in the DAD and NACRS databases. Statistical Methods: The self-controlled case series design (SCCS) was used to calculate the relative incidence of admissions, ER visits and other AEFIs. To investigate relative incidence for AEFIs across risk groups of interest, as well as addressing the healthy vaccinee effect bias, RIRs were calculated. RIRs are the ratio of incidence ratios in a subgroup of interest relative to a designated reference group. Results and Conclusions: The combined approach of using the SCCS design and RIRs to identify risk factors and overcome the healthy vaccinee bias proved to be a powerful approach to studying vaccine safety. Future work will be important to characterize the performance and validity of the SCCS + RIR approach in the presence of increasing levels of confounding and differing manifestations of the healthy vaccinee bias, as well as to elucidate the biological and behavioural mechanisms underlying our findings.
Keywords: Vaccine Safety; Self Controlled Case Series; Adverse events following immunization